Financial Performance Analysis And Stock Valuation of PT Kimia Farma Tbk. - Wiranti Wiranti; Oktofa Yudha Sudrajad (PT. Publikasiku Academic Solution, 2024)
Laparoscopic cholecystectomy is the surgical method of choice for gallbladder removal. Enhanced Recovery After Surgery (ERAS) is a program designed to accelerate patient recovery after surgery by reducing length of stay, pain, and accelerating initial mobilization. This study aims to evaluate the effectiveness of the ERAS nursing program on pain levels, initial mobilization, and length of hospitalization of post-laparoscopic cholecystectomy patients at Pluit Hospital Jakarta. A total of 65 patients undergoing laparoscopic cholecystectomy were sampled, with 40 patients in the ERAS group and 25 patients in the control group. Data were collected using questionnaires and observation sheets, and analyzed using the ANCOVA test. The results showed that the ERAS group had lower numerical scale scores for pain (1.87 vs 5.72, p < 0.001), earlier mobilization (3.45 hours vs 9.12 hours, p < 0.001), and shorter length of stay (27.13 hours vs 74.84 hours, p < 0.001) compared to the control group. The implementation of the ERAS nursing program has proven to be effective in reducing pain levels, accelerating initial mobilization, and reducing the length of stay of patients after laparoscopic cholecystectomy at Pluit Hospital Jakarta. This study supports the use of ERAS protocol to improve the quality of surgical care in Indonesia.